Saluyot Puto (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2019)
Puto is one of the most common, yet still loved delicacies of the Filipinos. Flour is one of the ingredients used in making puto. The type of flour used is vital at getting the right results in the end product. To create an end product, saluyot was seen as a potential option for flour production. Saluyot is a very abundant vegetable in the Philippines, which boasts many health benefits. Thinking of the possibility of producing flour, the researchers tried saluyot. Thus saluyot flour became the main ingredient in the product of this study. This study made use of the experimental-feasibility research design. A survey questionnaire on the level of acceptability of the product along different areas was answered by the students, teachers, and parents of UCC. Both descriptive and inferential statistics were used in this study. The respondents regarded all proportions as highly acceptable, and the 50% –50% proportion was the most favorable one among the rest. All indicators were rated very highly acceptable by the three groups of respondents. Results further revealed that there is a significant difference between the two sample proportions on the taste, aroma, and texture. The formulation of the business plan is recommended since the saluyot puto is highlyaccepted. Conventional recipes use specific ingredient measurements. Food innovation incorporates different ingredient ratios to attain positive acceptance of the consumers. At a consumer level, no-one likes surprises. One indicator may be overshadowed by another but that does not make them any less important to the food industry. Based on different researches people often select foods because of the nutrients it contains.
Keywords: saluyot, puto, feasibility study